Extension Block Pinning Vs Single Kirshner Wiring To Treat Bony Mallet Finger. A Retrospective Study. - Rocchi, Lorenzo; Fulchignoni, Camillo; De Vitis, Rocco; Molayem, Iakov; Caviglia, Daniele (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Bony Mallet Finger or Mallet Fracture is a common injury of the hand, which follows a forced flexion of the extended distal interphalangeal joint, that leads to a bony avulsion of the distal phalanx. Depending on fracture extension and dislocation, those lesions can either be treated conservatively or surgically. Several surgical options have been described in the literature. The aim of this study is to compare retrospectively two percutaneous pinning techniques: the extension block technique according to Ishiguro vs an original single Kirshner wiring (Umbrella technique).Methods: Between January 1998 and December 2019, among all patients treated surgically for a Mallet Fracture with either the Ishiguro’ and the Umbrella technique, 98 have been included in this study. All patients have been assessed one year after surgery using the Crawford method.Results: With both techniques better results have been achieved in younger patients and for those treated early. The umbrella technique seems to have better results in patients with fracture classified as 2b or 2c (Wehbe and Schneider classification), whereas the Ishiguro technique seems more appropriate for patients with a 1b fracture. Complication rate and typology vary depending on the used technique.Conclusions: The Ishiguro’ and the Umbrella technique both lead to good results for the treatment of surgical Mallet Fractures. The choice of the best type of pinning should mainly depend on fracture extension and time elapsed from trauma.